An overview of smart agriculture using internet of things (IoT) and web services - Vijaya Choudhary; Paramita Guha; Giovanni Pau; Sunita Mishra (Environmental and Sustainability Indicators)
The presented work provides an insightful overview of the Internet of Things (IoT), emphasizing its role in enabling real-world objects to communicate through networking technologies. IoT integrates wireless sensor networks, artificial intelligence, and cloud computing to boost productivity while minimizing costs and losses. The abstract underscores the importance of GUI applications for user-friendly interaction with IoT systems and the widespread use of RFID for tracking items, especially in supply chain management and inventory tracking. IoT devices equipped with RFID tags are highlighted as integral components of a broader network, with cloud computing offering a scalable infrastructure to manage the substantial data generated by IoT components. Data collection in IoT relies heavily on wireless sensor networks, with data uploaded to the cloud for synchronized analysis. The abstract suggests a comprehensive exploration of IoT applications across various fields, with a focus on smart-enabled applications. Overall, it sets the stage for a detailed examination of IoT's impact and potential in diverse contexts.